The typology and cultural-historical conditions of political leadership in the Balkans - Dymarski, Mirosław (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The aim of the paper is to analyze the types and determinants of political leadership in the Balkans. Were these types the copies of the Ottoman model of power, did they reflect native models or were some other models adapted? The theoretical part of the article is based on the cultural theory of leadership (A. Wildavski). Wildavski formulates the thesis that historical and cultural determinants allow us to assume the existence of political leadership in the Balkans, namely, all forms of strong leadership: despotic, absolutist, autocratic and dictatorial (Serbia, Bulgaria, Montenegro). Our considerations concern the period from the national uprisings in the Balkans in the 19th c. until the middle of the 20th c., so till the times when the Ottoman heritage could influence the political and social life in the collective memory. The situation of Europe after 1945 changed radically due to establishing communist states in the Balkan Peninsula and the appearance of an utterly different type of political power. The paper formulates as well the second main thesis that the general leadership in the Balkans in the 19th – 20th cs. was based on shortages: the shortage of political and legal culture, the shortage of elites, of social power, security, education, traffic routes (disintegration), cities and townsfolk etc. All this impeded social development and facilitated the appearance of strong, patriarchal leadership in its different forms. Not all cultural factors and historical heritage affected the character of leadership in an equally powerful manner, but one can distinguish the common core.